A systematic planning scheme for deployment of technology combined lean implementation framework - Rafique, M.Z.; M.N.A. Rahman,; Raheem, A.; Leuveano, R.A.C.; N. Saibani,; N. Arsad,; W.H.W. Mahmood,; Amjad, M.S. (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this modern age, use of technology combined lean implementation framework seems beneficial which not only helps in lean implementation but also contributes to speed up the process with the availability of proper planning scheme. However, based on previous literature available, a gap has been observed regarding the availability of “Systematic Planning Scheme” which is essential for the deployment of technology combined lean implementation frameworks. Based on this, the aim of this study is to propose “Systematic Planning Scheme” for such frameworks and since, lean has its stakes in a wide range of sectors but carries the maximum stake in the automotive industry (based on literature review utilized) so it is feasible to develop planning scheme for automotive sectors. With the help of data collection methods that have been utilized were field observations, on-site plant visits, and organizational documents in case study, a Systematic Planning Scheme has been developed. The designed systematic planning scheme critically required three steps which were team selection, phase wise distributions of work, and access to lean tools for lean implementation (by the team to implement framework. The contribution and significance of this study is the provisions of new planning strategy which carried originality in its structure by following three goal steps and visions to implement modern frameworks in a systemized way.